Production Performance, Meat Quality, and Lipid Profile of Broiler Duck Fed Diets Containing Selenium-Rich Hermentia illucens Larval - Kurniawan, D.; Widodo, E.; Susilo, A.; Sjofjan, O. (Faculty of Animal Science, IPB University, 2025)
The purpose of this study was to determine the effects of Se-enriched Hermetia illucens larvae meal (Se-BSFL) on the production performance, meat quality, and lipid profile of broiler ducks. A total of 250 one-day-old, unsexed hybrid broiler ducklings were randomly allocated into five dietary treatment groups, each with five replications of 10 ducklings, namely a control diet (T1), and control with added 5% (T2), 7.5% (T3), and 10% (T4) Se-BSFL, and a positive control diet with 10 mg/kg Se-Yeast (T5) for 42-days. Feed intake and body weight were measured on a weekly basis. At the end of the trial, one bird was selected from each replicate and sacrificed to determine carcass composition and blood serum profiles. The results indicated that dietary supplementation of 5% Se-BSFL resulted in higher final body weight, body weight gain, feed intake, and lower feed conversion ratio than the Se-yeast supplemented diet. Supplementation of Se-BSFL at 5% to 10% significantly affected (p<0.05) high-density lipoprotein, low-density lipoprotein, cholesterol, and triglyceride compared to those of T1 and T5. Supplementation with 5% and 7.5% Se-BSFL (p<0.05) has higher levels of monounsaturated fatty acids in comparison to T1 and T5. Moreover, the supplementation of Se-BSFL did not influence the physical quality of the meat. In conclusion, feeding Se-BSF at 5% is recommended in diets as it does not negatively affect production performance and carcass traits. These findings suggest that the inclusion of Se-BSFL in broiler duck diets enhances their fatty acid and serum lipid profiles, indicating potential benefits from the use of Se-BSFL as a feed component in poultry production.